'This is a House': Large Image Collections and Their Platform Embeddings. (February 2023) - Mackenzie, Adrian
This paper analyses the active role of image collections in supporting platforms and their operations. Large image collections are increasingly present on media, scientific and other platforms. A case study of Facebook's predictive modelling of satellite images of human settlement exemplifies how image collections are changing. The treatment of images in a predictive model – a deep neural network – constructs a condensed indexical field, a field that allows the platform to generate referential statements about the world. Under platform conditions, image collections function less as archives or records and more as densely woven indexical fields that orient, position and embed the platform. In describing the transformation of image collections, the paper points to important changes in how platforms use images to position themselves in the world.